OCCURRENCE OF SALIVARY GLANDS TUMOURS A FIFTEEN YEARS EXPERIENCE - Ahmad, Sajjad; Wahid, Abdul; Qayum, Iftikhar; idrees, Muhammad (Journal of Ayub Medical College Abbottabad, 1998)
This is an analysis of 35 salivary gland tumours from local tumour registry1 showing early age female predilection. Twenty out of 35 (57.14%) cases were female. 15/35 (42.86%) cases were male. The ages ranged between 15 to 80 years with maximum number of cases (21/35, 60%) in the age group below 40 years and mostly female (57%).